MO633GLYCAEMIC MARKERS IN PATIENTS WITH TYPE 2 DIABETES UNDERGOING HAEMODIALYSIS EVALUATED BY LONG-TERM CONTINUOUS GLUCOSE MONITORING*. (29th May 2021) - Bomholt, Tobias; Rix, Marianne; Almdal, Thomas Peter; Knop, Filip K; Rosthøj, Susanne; Heinrich, Niels Søndergaard; Jørgensen, Morten; Larsson, Anders; Hilsted, Linda; Feldt-Rasmussen, Bo; Hornum, Mads
Abstract: Background and Aims: The reliability of haemoglobin A1c (HbA1c) as a glycaemic marker in patients receiving haemodialysis (HD) remains unknown. To assess accuracy, we compared HbA1c and fructosamine levels with interstitial glucose levels measured by continuous glucose monitoring (CGM) in patients with type 2 diabetes receiving HD. Method: The HD group (maintenance HD and type 2 diabetes) comprised 30 patients who completed the study period of 17 weeks; the control group (type 2 diabetes and an estimated glomerular filtration rate >60 mL/min/1.73 m 2 ) comprised 36 individuals. CGM (Ipro2 ®, Medtronic) for periods up to seven days was performed five times (with four weeks intervals) during a 16-week period. HbA1c and fructosamine were measured at week 17. The mean sensor glucose from CGM was compared with the measured HbA1c, its estimated mean blood glucose (eMBGA1c ) and fructosamine levels. Results: In the HD group, the mean sensor glucose from CGM was 1.4 (95% confidence interval [CI]: 1.0–1.8) mmol/L higher than the eMBGA1c, whereas the difference was 0.1 mmol/L (95% CI: -0.1–[0.4]; P <0.001) in the control group. Adjusted for the mean sensor glucose, HbA1c was -7.3 (95% CI: -10.0–[-4.7]) mmol/mol lower in the HD group than in controls ( P <0.001), whereas no difference was detected for fructosamine ( P =0.64). Conclusion: HbA1c evaluated by CGM underestimates mean blood glucose levels in patients receiving maintenance HD; fructosamine appears to be more accurate. CGM-assessed blood glucose could complement or replace HbA1c in patients where HbA1c underestimates blood glucose levels.